2022
DOI: 10.1002/adfm.202211467
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Optoelectronic Synaptic Devices Based on Metal Halide Perovskites

Abstract: Massive data processing with high computing efficiency and low operating power is required owing to the rapid development of artificial intelligence and information technology. However, the von Neumann structure computing system with the separated memory and processor can cause large energy consumption and a low running speed during massive data processing. Therefore, the brain-inspired neuromorphic computing system is developed, that can provide hardware support for emulating biological synaptic functions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 140 publications
0
27
0
Order By: Relevance
“…Photonic and electronic logic circuits play a crucial role in the development of integrated circuits, which consist of optoelectronic logic gates . These logic gates enable digital matrix calculation, leading to improved efficiency by reducing data volume in a computing system. Consequently, they are regarded as a pivotal element in the advancement of future integrated circuits and high-speed computing systems. The light pulse and gate voltage pulse serve as logic input terminals (p and q), while the transistor current represents the logic output terminal (s).…”
Section: Resultsmentioning
confidence: 99%
“…Photonic and electronic logic circuits play a crucial role in the development of integrated circuits, which consist of optoelectronic logic gates . These logic gates enable digital matrix calculation, leading to improved efficiency by reducing data volume in a computing system. Consequently, they are regarded as a pivotal element in the advancement of future integrated circuits and high-speed computing systems. The light pulse and gate voltage pulse serve as logic input terminals (p and q), while the transistor current represents the logic output terminal (s).…”
Section: Resultsmentioning
confidence: 99%
“…[3] Halide perovskites have ABX 3 structure, where A is a monovalent organic cation such as methylammonium and formamidinium, B is a divalent metal cation such as Pb 2+ or Sn 2+ , and X is a halide such as Cl − , Br − or I − , has emerged as a potential candidate owing to their high defect tolerance, low defect formation energies, compositional and optical bandgap flexibility, and light/electric pulse induced stimulation possibilities. [4][5][6][7][8][9][10] The key processes, such as hysteresis, defect formation, and non-radiative recombination, which are detrimental to photovoltaic application act as favorable characteristics for the neuromorphic synaptic devices. Recently, methylammonium lead triiodide (MAPbI 3 ) based synaptic devices exhibiting synaptic behaviors concerning photonic and electronic stimulations were reported.…”
Section: Introductionmentioning
confidence: 99%
“…5 Most reported synaptic devices showed energy consumption above a picojoule, which is much higher than that of biological synapses. 17,18 To solve such problem, self-powered technologies provide a promising way. ]thiadiazole) and tellurophene, a narrow-band conjugated polymer with a high dielectric constant.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, the energy consumption of each synapse in the brain is about 10 fJ per synaptic event . Most reported synaptic devices showed energy consumption above a picojoule, which is much higher than that of biological synapses. , To solve such problem, self-powered technologies provide a promising way. Chen et al reported a flexible and self-powered optical synapse based on the copolymer of 4,8-di­(thiophen-2-yl)-1|2,3|2-benzo [1,2-c:4,5-c’]­bis­([1,2,5]­thiadiazole) and tellurophene, a narrow-band conjugated polymer with a high dielectric constant . The authors ascribed the self-powered properties to spontaneous exciton dissociation caused by both the localized electric field of the polyethylene terephthalate (PET) substrate and the high dielectric constant of the narrow-band conjugated polymer .…”
Section: Introductionmentioning
confidence: 99%